Application of the use of Modern Dressing in the Healing Process of Diabetic Foot Ulcus - Dwiani Kartika; Niken Sukesi (GLOBAL HEALTH SCIENCE GROUP, 2022)
Diabetic foot ulcers are open sores that occur on the feet of DM patients caused by repeated pressure on the feet and is accompanied by the presence of peripheral neuropathy, deformity of the foot and development of infection which often complicates healing due to reduced arterial circulation. One alternative to pharmacological treatment is wound care with modern dressing, the purpose of choosing modern dressings is to support the wound healing process. The purpose of the study was to determine the application of modern dressings to the healing process of diabetic foot ulcers at the Erbe Mowcare Clinic, Pekalongan. The method used is descriptive to explain how the application of modern wound care dressings to the wound healing process in diabetic foot ulcer patients. This study provides intervention to 4 respondents who will be treated and compare the results before and after modern wound dressing with the observation sheet BatesJansen Assessment Wound Tool. The results obtained based on the Bates-Janes Assessment Wound Tool showed that the four respondents experienced positive changes in the wound healing process. Respondent 1 got a score of 25 to 18 in the wound regeneration, while respondent 2 got a score of 31 to 22 in the wound regeneration category. Respondent 3 got a score of 43 to 16 in the wound regeneration. Respondent 4 got a score of 45 to 28 with the category of wound regeneration. The application of modern dressing on the four respondents had an influence on the healing process of diabetic ulcers.